Physical Sanitation of the House that Influence the Incidence of ARI in Children under Five in Kalianget Timur Village - Adhasari Agungnisa (JURNAL KESEHATAN LINGKUNGAN, 2019)
Physical sanitation of the house and parent's behavior are the factors that could affect the incidence of ARI in children under five. The aim of this research was to analyze what factors of house physical sanitation that affect the occurrence of ARI among children under five in East Kalianget Village. This research was an observational research, with cross sectional design. The samples in this research were 60 children under fives randomly chosen through simple random sampling. Data collection was done through interview, observation, thermohygrometer, roll meter, lux meter, and EPAM 5000. Data was analyzed using chi-square and binary logistic regression analysis. The results showed that children under five's bedroom density (p=0.241) was affecting the occurrence of ARI among children under five, meanwhile ventilation area (p=0.241), air temperature (p=0.948), humidity (p=0.830), and lighting (0.393) were not affecting the occurrence of ARI among children under five. Communities of East Kalianget Village that have unsuitable occupancy density are suggested to reset the number of their bedroom's occupants, for example maybe a father sleeping in the living room to prevent the occurrence of ARI among children under five.